2006
DOI: 10.1111/j.1468-3083.2006.01570.x
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiology study of patients with uremic pruritus

Abstract: This study showed us that uremic pruritus was observed more in men than women. The high prevalence of uremic pruritus in our study does not support the decrease of pruritus due to an improvement in the management of dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 18 publications
7
78
2
4
Order By: Relevance
“…Mistik et al reported that 50.2% of the patients that received hemodialysis treatment had pruritus at the time of the study period (10). Various related studies have stated that 22-90% of the patients suffered from pruritus (2,9-16).…”
Section: Discussionmentioning
confidence: 99%
“…Mistik et al reported that 50.2% of the patients that received hemodialysis treatment had pruritus at the time of the study period (10). Various related studies have stated that 22-90% of the patients suffered from pruritus (2,9-16).…”
Section: Discussionmentioning
confidence: 99%
“…Uremic itch is believed to be the result of a complex contribution of numerous uremic and non-uremic factors. Known risk factors predisposing to uremic pruritus include male gender, 18 elevated serum levels of calcium, phosphorus, magnesium, urea, and β 2 -microglobulin. 19,20 Other contributing factors comprise xerosis, anemia, high serum aluminum level, increased calcium × phosphate product, hypervitaminosis A, erythropoietin insufficiency, low albumin, low transferrin, elevated ferritin, secondary hyperparathyroidism, dialysis membrane material, inefficient dialysis, systemic inflammation, uremic neuropathy, allergic sensitization, elevated serum histamine level, intradermal mast cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence regarding the relationship between the onset and severity of pruritus and the duration of ESRD and dialysis therapy (11,12,16). No clear association between pruritus and underlying renal disease has been established (12). The proportion of ESRD patients with uremic pruritus has decreased significantly with modern dialysis from approximately 85% in the 1970s to the present day rate of 40%-50% (11,17,18).…”
Section: Nonspecific Manifestationsmentioning
confidence: 99%
“…The exact pathophysiology of uremic pruritus is unknown, but it is likely multifactorial. Possible etiological factors are presented in Table 2 (11)(12)(13)(14)(15). There is conflicting evidence regarding the relationship between the onset and severity of pruritus and the duration of ESRD and dialysis therapy (11,12,16).…”
Section: Nonspecific Manifestationsmentioning
confidence: 99%